Recurrent spontaneous multiple pregnancy: a case report - Parveen, Shazia; Sabzposh, Noor Afshan; Kuraishy, Amina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Multiple gestations are usually iatrogenic like use of assisted reproductive techniques (ART), infertility treatment but it is rare in spontaneous conception. High order multiple pregnancies (HOMPs) are major cause of maternal, fetal and neonatal morbidity. Multiple gestations carries 2 complications either abortion in early gestation or a preterm delivery in late pregnancy (more common). Preterm delivery is common (50%) and patient usually delivers by 30-32 weeks. Discordance of fetal growth is very common and even more than in twins. Perinatal loss is inversely related to birth weight. The mothers should be counseled about regular ante natal care (ANC) check-ups for early identification of multiple pregnancies so that proper care can be given to prolong the gestational age and reduce the complications associated with multiple pregnancies.